Agricultural support measures of advanced countries and food insecurity in developing countries - Michael Herrmann (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Many developing nations, especially the least developed countries, are subjected to recurrent spells of food insecurity. In order to understand food insecurity in these countries it is necessary to consider not only immediate or trigger-causes of food crises, but also its underlying or systemic causes. This paper argues that the agricultural support measures of advanced countries may act as a systemic cause for food insecurity in developing countries. While the import of subsidized foods by developing countries and/or the provision of food aid by developed countries are frequently necessary options to address food crises in the short run, they can adversely affect the economic development in the long run. Access to cheap foods can undermine agricultural production and contribute to the recurrence of food shortages. This paper examines these developments and makes proposals to address them.
Keywords: Q17; Q18; O13; O18; O19; F13; F42; 330; food insecurity; agricultural support; rural development; LDCs; Nahrungsmittelversorgung; Agrarproduktion; Internationale Arbeitsteilung; Ländliche Entwicklung; Entwicklungsländer